New-onset egg allergy in an adult: A case report - Fujiwara, Michimasa; Kimura, Takashi; Ohira, Junya; Inotani, Motohiro; Sakane, Tomoko; Iwase, Mizue; Yamashita, Sadanori; Araki, Tooru (Frontiers in Allergy, 2024)
Most adult cases of hen's egg allergy are carried over from childhood, and new-onset adult cases are rare. Such cases may result from cross-reactivity or sensitization by inhalation. Here we present a rare case of adult-onset egg allergy due to monosensitization to ovalbumin (Gal d 2) with an unclear sensitization pathway. A 27-year-old woman developed recurrent gastrointestinal symptoms after ingestion of raw and under-cooked eggs. She had never suffered from atopic dermatitis or food allergies. She had never kept birds as pets and had no history of exposure to egg allergens. Prick to prick testing was positive only with raw egg white. Specific IgE testing revealed monosensitization to Gal d 2. She was advised to avoid raw and undercooked eggs and her symptoms resolved. In the management of adult-onset egg allergy, evaluation of allergen components will lead to appropriate elimination guidelines, and investigation of sensitization pathways may help identify the cause of this disease.